2022
DOI: 10.1186/s12955-022-01993-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of a German version of the Multimorbidity Treatment Burden Questionnaire

Abstract: Background Patients with multiple long-term conditions often face a variety of challenges arising from the requirements of their health care. Knowledge of perceived treatment burden is crucial for optimizing treatment. In this study, we aimed to create a German version of the Multimorbidity Treatment Burden Questionnaire (MTBQ) and to evaluate its validity. Methods The steps to translate the MTBQ included forward/back translation, cognitive interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
4
0
4
Order By: Relevance
“…The high Kaiser-Meyer Olkin value (0.773) and the statistically significant Bartlett test of sphericity result ( p < 0.001) indicated sampling adequacy and were close to the values obtained in the previous validation studies [ 12 , 14 ]. The factor analysis of the question items suggested a three-factor solution, similar to two of the previous MTBQ validation studies [ 14 , 15 ]. The results showed that the Lithuanian version of MTBQ has high internal reliability, good construct validity and factor dimensionality.…”
Section: Discussionsupporting
confidence: 77%
“…The high Kaiser-Meyer Olkin value (0.773) and the statistically significant Bartlett test of sphericity result ( p < 0.001) indicated sampling adequacy and were close to the values obtained in the previous validation studies [ 12 , 14 ]. The factor analysis of the question items suggested a three-factor solution, similar to two of the previous MTBQ validation studies [ 14 , 15 ]. The results showed that the Lithuanian version of MTBQ has high internal reliability, good construct validity and factor dimensionality.…”
Section: Discussionsupporting
confidence: 77%
“…A significant negative correlation was found between the global MTBQ and the EQ-5D-index, in line with previous findings. [ 22 , 30 ] Significant differences were also observed in the mean EQ-5D-index and EQ-VAS score among the treatment burden strata. Post-hoc analyses demonstrated significant differences among the treatment burden groups.…”
Section: Discussionmentioning
confidence: 98%
“…The Multimorbidity Treatment Burden Questionnaire(MTBQ) was originally developed and validated in United Kingdom (UK) [20], and has been translated into Danish [21], German [22] and French Canadian [23], demonstrating good content validity, construct validity and reliability. The Chinese Multimorbidity Treatment Burden Questionnaire (C-MTBQ) [10]was translated, culturally adapted and validated, to assess the treatment burden of multimorbidity in China.…”
Section: Measures Treatment Burdenmentioning
confidence: 99%
“…The global MTBQ score is calculated as the mean score, multiplied by 25, giving a score of 0 to 100. Global treatment burden scores can be categorized as: no (0), low (< 10), medium (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and high treatment burden (≥22) [20].…”
Section: Measures Treatment Burdenmentioning
confidence: 99%